A risk score based on simple angiographic characteristics to aid in choosing the optimal revascularization strategy for patients with multivessel disease presenting with ST-elevation myocardial infarction. Issue 7 (November 2020) - Schamroth Pravda, Nili; Witberg, Guy; Zusman, Oren; Landes, Uri; Bental, Tamir; Assali, Abid; Vaknin Assa, Hana; Greenberg, Gabriel; Codner, Pablo; Perl, Leor; Kornowski, Ran
Abstract : Background: The optimal revascularization strategy is not clearly defined for patients with ST-elevation myocardial infarction with multivessel disease (MV-STEMI). We aimed to develop a simple angiographic risk score for identifying patients with MV-STEMI that might benefit from a multivessel percutaneous coronary intervention (MV-PCI), compared to a PCI for only the infarct-related artery (IRA-PCI). Methods and results: This retrospective study acquired data from a single-center STEMI registry on 841 consecutive patients with MV-STEMI (645 IRA-PCI and 196 MV-PCI). Patients were stratified according to high- and low-risk scores. We devised a score based on three characteristics of non-culprit lesions previously reported to predict overall mortality (proximal left anterior descending artery involvement, maximal % stenosis, and number of involved vessels). The primary endpoint was major adverse cardiac events (MACEs: a composite of death/MI/urgent repeat revascularization). After a median follow-up of 1909 days, MACE occurred in 205/841 (24.4%) patients. MACE risk was higher in the high-risk than in the low-risk group (HR 1.43, P < 0.001). In comparing the IRA-PCI and MV-PCI approaches within each risk group, we found that these revascularization strategies had differential effects on outcome. Compared to the MV-PCI, IRA-PCI was associated with less MACE in the low-risk group (HR 0.597, P = 0.033), and more MACE in the high-risk group (HR 3.14, P < 0.001). Conclusion: For patients with MV-STEMI that undergo primary PCI, a simple risk score based on three angiographic characteristics could identify patients at high risk of future adverse events. This score might facilitate choosing the optimal revascularization strategy. Abstract : Supplemental Digital Content is available in the text.